A Bionic Interface to Suppress the Coffee-Ring Effect for Reliable and Flexible Perovskite Modules with a Near-90% Yield Rate - Fan, Baojin (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.